Architecture, place and identity: An exploration through an interpretive pattern language tool. A case study of Khartoum’s City Centre (KCC) - Sudan - Hamid, Malathe (2020)
This research commenced from a broader background in postcolonial architectural studies with a special interest in Khartoum the capital city of Sudan as a postcolonial city. However, this was restrained by the scarcity of the architectural research that comprehensively portrays its architecture. Consequently, this has determined the exploratory nature of the research which started with photographic documentation and series of observations coupled with reviewing the existing, but limited, research on Khartoum’s architecture. This has resulted in classifying the architecture of Khartoum into architectural paradigms denoting the architectural styles that appeared in the different historical periods. Yet, to narrow down this exploration, Khartoum’s city centre (KCC) has been selected as the research’s case study. Nevertheless, the uniqueness of this case study, expressed by the interplay of its urban formation as a place, the Juxtaposition of its different historical architectural layers including colonial architecture, modern architecture and its current contemporary architecture and its identity as a postcolonial place, acted as the research’s main angles to be explored.